Prevention of gastric mucosal injury induced by anti‐platelet drugs by famotidine. (21st March 2014) - Uotani, Takahiro; Sugimoto, Mitsushige; Nishino, Masafumi; Ichikawa, Hitomi; Sahara, Shu; Yamade, Mihoko; Iwaizumi, Moriya; Yamada, Takanori; Osawa, Satoshi; Sugimoto, Ken; Umemura, Kazuo; Watanabe, Hiroshi; et al.
Abstract Anti‐platelet drug‐induced gastric mucosal injury correlates with intragastric pH. Our aim was to investigate prophylaxis effects of famotidine, one of the representative histamine‐2 receptor antagonists (H2RA), on gastric mucosal injury induced by dual therapy with low‐dose aspirin and clopidogrel in relation to Helicobacter pylori (H. pylori) infection and CYP2C19 genotypes. This study was conducted for 20 healthy Japanese volunteers (10 H. pylori‐positive and 10‐negative subjects) with 100 mg aspirin plus 75 mg clopidogrel (AC) once‐daily dosing and AC plus 20 mg famotidine twice‐daily dosing (ACH). Mucosal injury was endoscopically assessed on day 3 and 7 and 24‐hour intragastric pH and antiplatelet‐function test was performed on day 7. Median pH in ACH was similar between CYP2C19 extensive metabolizer (EM) and intermediate metabolizer (IM)/poor metabolizer (PM) and was significantly higher in H. pylori‐positive than negative subjects (P < .05). Mucosal injury with ACH significantly decreased in both day 3 and 7 compared with AC, irrespective with H. pylori and CYP2C19 genotypes (P < .05). Although antiplatelet effect of clopidogrel in EM was significantly higher than that in IM/PM, the additional famotidine did not affect the effect. Anti‐platelet drug‐induced gastric injury was alleviated by famotidine without attenuation of anti‐platelet functions irrespective of H. pylori and CYP2C19 genotypes.